1987
DOI: 10.1115/1.3262122
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Aerodynamic Interactions in a Multistage Compressor

Abstract: The fundamental flow physics of multistage blade row interactions is experimentally investigated, with unique data obtained which quantify the unsteady harmonic aerodynamic interaction phenomena. In particular, a series of experiments is performed in a three-stage axial flow research compressor over a range of operating and geometric conditions at high reduced frequency values. The multistage unsteady interaction effects of the following on each of the three vane rows are investigated: (1) the steady vane aero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…One of the first studies of airfoil clocking was performed by Capece (1987), who showed the potential performance benefits. Saren et al (1994Saren et al ( ,1995Saren et al ( ,1997 have used theoretical, computational and experimental techniques to show that airfoil clocking can be used to increase performance and reduce unsteady aerodynamic loads on airfoils.…”
Section: Introductionmentioning
confidence: 99%
“…One of the first studies of airfoil clocking was performed by Capece (1987), who showed the potential performance benefits. Saren et al (1994Saren et al ( ,1995Saren et al ( ,1997 have used theoretical, computational and experimental techniques to show that airfoil clocking can be used to increase performance and reduce unsteady aerodynamic loads on airfoils.…”
Section: Introductionmentioning
confidence: 99%
“…The blade mounted transducers are statically calibrated to determine sensitivity and to insure linearity. A dynamic calibration (Capece and Fleeter, 1987) showed negligible phase shift and attenuation to 2100 Hz, three times the impeller blade pass frequency. The unsteady static pressure at the impeller exit/diffuser entrance is measured using PCB Piezotronics 103A piezoelectric transducers.…”
Section: Unste Dy Pressure Instrumentationmentioning
confidence: 95%
“…One of the first studies of airfoil clocking was performed by Capece (1987), who showed the potential performance benefits. Saren et al (1994Saren et al ( ,1995Saren et al ( ,1997Saren et al ( ,1998 et al (1998) and Cizmas et al (1997Cizmas et al ( , 1998 Baldwin and Lomax (1978) was used in this study.…”
Section: Introductionmentioning
confidence: 99%